Proceedings of the 27th Conference on Image and Vision Computing New Zealand 2012
DOI: 10.1145/2425836.2425888
|View full text |Cite
|
Sign up to set email alerts
|

A dissection of fingerprint fuzzy vault schemes

Abstract: The fuzzy vault construction is one of the most widely adopted approaches for the protection of fingerprint data. The popularity of this scheme stems from its ability to deal with unordered sets of fingerprint features, as well as its tolerance to missing or spurious feature elements across multiple acquisitions of the same fingerprint. While a considerable number of fingerprint-based fuzzy vault implementations have been reported in the literature, a review of these schemes does not yet exist, to the best of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The vault can only be unlocked if there is another set of data which significantly overlaps with the original data. The generic fuzzy vault is suitable for unordered feature sets (such as fingerprints) and does not suffer performance degradation due to missing or spurious feature elements in multiple acquisitions of the same biometric data [49]. Fuzzy vault has been widely used to protect stored templates in automatic fingerprint verification systems [50,51].…”
Section: Fuzzy Vaultmentioning
confidence: 99%
“…The vault can only be unlocked if there is another set of data which significantly overlaps with the original data. The generic fuzzy vault is suitable for unordered feature sets (such as fingerprints) and does not suffer performance degradation due to missing or spurious feature elements in multiple acquisitions of the same biometric data [49]. Fuzzy vault has been widely used to protect stored templates in automatic fingerprint verification systems [50,51].…”
Section: Fuzzy Vaultmentioning
confidence: 99%
“…Building upon this preliminary analysis, a series of implementations for minutiae-based fingerprint fuzzy vaults was proposed [57], [58]. A useful guide for constructing a fuzzy vault scheme is provided in [59]. Different security analyses have found that the original fuzzy vault scheme is vulnerable to a certain kind of linkage attack, i.e.…”
Section: Fuzzy Vault Schemementioning
confidence: 99%
“…Hash functions are employed in our construction to further protect each single biometric trait. A dissection of fingerprint fuzzy vault schemes" the university of auckland new zealand, [4] vedrana krivokuća, waleed abdulla, akshya swai 2014. In this paper the fuzzy vault construction is adopted for the protection of fingerprint data.An alignment-free fingerprint cryptosystem based on fuzzy vault scheme, Journal of network and computer applications, peng li , xinyang , kaicao , xunqiangtao, ruifangwang , jietian 33 (2010) 207-220 [1].…”
Section: IImentioning
confidence: 99%